Scaling physiological processes : leaf to globe - Ehleringer, J. R.; Field, Christopher B. (Physiological ecology., 1993)
Traditional plant physiological ecology is organism centered and provides a useful framework for understanding the interactions between plants and their environment and for identifying characteristics likely to result in plant success in a particular habitat. This book focuses on extending concepts from plant physiological ecology as a basis for understanding carbon, energy, and biogeochemical cycles at ecosystem, regional, and global levels. This will be a valuable resource for researchers and graduate students in ecology, plant ecophysiology, ecosystem research, biometerology, earth system science, and remote sensing. Key Features * The integration of metabolic activities across spatial scales, from leaf to ecosystem * Global constraints and regional processes * Functional units in ecological scaling * Models and technologies for scaling.